Jejeran: Interactive Game-Based Flash Media as Social Studies Learning Media in Elementary Schools - Idammatussilmi; Ellianawati; Nur Wahyudi (Jurnal Ilmiah Sekolah Dasar, 2023)
Social studies learning in elementary schools has so far focused on conventional methods by giving verbal explanations. An innovation is needed that can help teachers carry out learning in an interesting, effective and efficient manner. One effort that can be done is to present an interactive flash technology-based learning media. The purpose of this study was to analyze the effectiveness of interactive game-based flash media as learning media in elementary schools. The research method used is research and development with the ADDIE model. This study involved teachers and 27 third grade students. Data collection techniques used are the results of unstructured interviews, observation, questionnaires, written questions (Pretest and Post-test). Product validity is obtained from expert validation and product trials. The results showed that the development of flash media based on interactive games was in the category of very feasible and very effective to use based on the feasibility test according to media experts with a total percentage of 90% and the due diligence according to material experts was 90.38%. This learning media was stated to be very effective based on the effectiveness test with the results of the small group test with a total percentage of 83.33% and the large group trial with a total percentage of 90.40%. In its application, the use of this media was able to increase the average value from 74.81 to 86.45 so that interactive game-based flash learning media was included in the category of very valid, very feasible and very effective.